Effects of plant growth-promoting rhizobacteria on growth indicators and physiological characteristics of Peucedanum praeruptorum Dunn leaves. (31st December 2023) - Zhang, Meng; Hua, Min; Guo, Dongqin; Xue, Yanbin; Chen, Xubing; Rui, Lu; Zhou, Nong
ABSTRACT: As a kind of medicinal plant, Peucedanum praeruptorum Dunn has been over-harvested in the wild population, which leads to its artificial cultivation. The present study aims to analyze the effects of different plant growth-promoting rhizobacteria (PGPR) on the growth and physiological characteristics of P. Praeruptorum leaves. Compared with the CK, the content of malondialdehyde (MDA) was drastically reduced in the leaves of P. Praeruptorum in different treatment groups ( P < 0.05), and with S6 showing the most significant reduction in MDA content (content was only about 1/3 that of the CK). The indicators of leaf area, length and width were found to be the highest in group S9, reaching a level that is 3.75, 3.08 and 1.48 times higher than those in group CK, respectively. Group S8 has the largest plant height, which is 1.22 times higher than that in group CK. S2 has the largest stem diameter, which is 1.69 times higher than that in group CK. Group S1 has the largest petiole length, which is 1.74 times higher than that in group CK. Group S6 has the largest chlorophyll content, which is 1.63 times higher than that in group CK. Group S2 has the highest content of soluble sugar and soluble protein, which are 2.02 times and 3.82 times higher than those in group CK. Group S9 exhibits the strongest CAT activity, which is 3.71 times higher than that in group CK. S5 exhibits the strongest SOD activity, which is 2.32 times higher than group CK. Group S1 exhibits the strongest POD activity, which is 5.94 times higher than that in group CK. In conclusion, the inoculation with PGPR is effective in improving the growth of P. Praeruptorum leaves and their physiological indicators, which provides guidance on the application of PGPR to achieve the high quality and yield of P. Praeruptorum .